PENGARUH PERBANDINGAN MOCAF (Modified Cassava Flour) DENGAN TEPUNG KACANG HIJAU (Vigna radiata) TERHADAP KARAKTERISTIK TUILE - Rianta, I Made Dwi Purnama; Ina, Putu Timur; Widarta, I Wayan Rai (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 8 No 3 (2019): Jurnal ITEPADO - 10.24843/itepa.2019.v08.i03.p08, 2019)
This research was conducted with the aims to determine the effect of mocaf and mung bean flour to the characteristics of tuile and get a certain ratio of mocaf and mung bean flour which able to produce tuile with the best characteristics. This research used randomized block design with treatment factor is the ratio of mocaf and mung bean flour which consist of 6 levels: 100%:0%; 90%:10%; 80%:20%; 70%:30%; 60%:40%; and 50%:50%. The treatment was repeated 3 times to obtain 18 units of experiment. The data were analyzed with Analysis of Variance method and if the treatment had an effect on the variable, the Duncan test were performed. The results showed that the ratio of mocaf and mung bean flour had an effect on water content, ash content, protein content, crude fiber content, carbohydrate content, color, taste (hedonic test), texture (hedonic test and scoring test) and overall acceptance (hedonic test). Ratio of 70% mocaf : 30% mung bean flour is the best characteristic with 1,16% water content, 1,46% ash content, 8,54% protein content, 15,49% fat content, 73,33% carbohydrate content, 5,36% crude fiber content, rather liked color, rather liked flavor, crunchy and liked texture, rather liked taste, and overall acceptance is rather liked. Keyword: mocaf, mung bean flour, tuile